A case report of a patient with chronic granulomatous disease complicated by invasive aspergillosis and disseminated Burkholderia multivorans infection - Xuanwen Weng; Heng Zhang; Pei Liu; Wei Gao; Huiping Li (Frontiers in Medicine, 2026)
Background Chronic granulomatous disease (CGD) is a rare inborn error of immunity characterized by defective phagocyte oxidative burst, leading to recurrent, life-threatening infections with catalase-positive bacteria and fungi. Co-infections with Aspergillus and Burkholderia species in CGD are exceedingly rare and often fatal due to synergistic pathogenic mechanisms and limited therapeutic options. Case presentation We report a fatal case of X-linked CGD in a 14-year-old male with a history of recurrent infections, who presented with severe pneumonia, respiratory failure, and profound growth retardation. Metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage fluid (BALF) identified Aspergillus flavus complex, Burkholderia multivorans , and subsequent cultures confirmed disseminated B. multivorans infection and invasive aspergillosis. Whole-exome sequencing revealed a novel missense mutation, c.1514T>A (p.Leu505Gln), in the CYBB gene, predicted to result in loss of NADPH oxidase function, which is consistent with the severe infectious phenotype observed. Despite aggressive antimicrobial therapy and intensive supportive care, the patient developed refractory septic shock and multiorgan failure, and died on day 14 of hospitalization. Conclusions This case underscores the lethal potential of concurrent Aspergillus and Burkholderia infections in X-linked CGD and highlights the critical importance of early diagnosis, which can be achieved through functional assays such as the DHR test or NBT test, followed by genetic confirmation when available. The novel CYBB mutation expands the known genotype-phenotype spectrum of severe X-CGD. Prompt recognition of primary immunodeficiencies in children with recurrent infections caused by typical pathogens is essential to enable timely prophylaxis and curative interventions such as hematopoietic stem cell transplantation before irreversible infectious complications occur.